THE DEVELOPMENT OF AN INTEGRATED PEST MANAGEMENT PLAN FOR ROOF RATS IN HAWAIIAN MACADAMIA ORCHARDS - Campbell, Earl W., III; Koehler, Ann E.; Sugihara, Robert T. (DigitalCommons@University of Nebraska - Lincoln, 1998)
Roof rats (Rattus rattus) damage an estimated 5 to 10% of the developing nut crop in Hawaiian macadamia (Macadamia integrifolia) orchards. Relevant aspects of roof rat biology in macadamia orchards have and continue to be studied with the ultimate goal of developing an ecologically sound and cost-effective integrated pest management plan. The field component of a two-year study of roof rat populations in macadamia orchards has recently been completed. The goal of this study is to clarify the relationship between roof rat seasonal abundance, macadamia flowering, and nut production on five orchards in three regions on the island of Hawaii. The authors herein present preliminary results from selected aspects of this research. This and other completed studies on rat feeding locations and the effect of simulated rat damage during different stages of nut development will aid in the determination of critical points in the crop cycle when rats cause significant economic damage and control of damage is warranted. This paper is intended to be an overview of research leading to the development of a realistic integrated pest management plan for roof rats in Hawaiian macadamia orchards.